IMPLEMENTASI MEAN FILTERING UNTUK MENGURANGI NOISE PADA CITRA DIGITAL - Manalu, Juliadi; Sinurat, Sinar (STMIK Budi Darma, 2017)
Improved image quality (image enhancement) is one of the early processes in image processing (image preprocessing). Improved quality is required because often the image used as the subject of discussion has poor quality, for example, the image is noise at the time of transmission through the transmission line, the image is too bright/dark, the image is less sharp, blurred, and so on. The mean filtering method is a filtering technique that works by replacing the intensity of a pixel with the average pixel value of pixels from neighboring pixels. If an image f (x, y) of size M x N is filtered by filter h (x, y) it will produce the image g (x, y), where filter h (x, y) is a matrix containing 1 / filter size. Mean filter the mean value of the data set. The mean filtering used for this smoothing effect is a type of spatial filtering, which in the process involves surrounding pixels.